2021
DOI: 10.1002/adom.202101945
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Functionalization of CsPbBrI2/SiO2 Core–Shell Nanocrystals Enhances the Stability and Efficiency in Electroluminescent Devices

Abstract: Surface ligand exchange on all‐inorganic perovskite nanocrystals of composition CsPbBrI2 reveals improved optoelectronic properties due to strong interactions of the nanocrystal with mono‐functionalized porphyrin derivatives. The interaction is verified experimentally with an array of spectroscopic measurements as well as computationally by exploiting density functional theory calculations. The enhanced current efficiency is attributed to a lowering of the charging energy by a factor of 2–3, which is determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Together with the changes in the PLQY of LiTFSI-treated CsPbBr 3 NC films, we also observed a slight red shift of their PL emission spectra (Figure S1), which is indicative of ligand exchange by the addition of LiTFSI to the NC solutions prior to spin-coating. Similar observations were recently reported on red-emitting LHP NC and were assigned to the highly dynamic/labile binding situation of oleic acid and oleylamine on the perovskite NC surface. , Therefore, both the enhanced PLQY and the spectral PL red shift indicate that the new ligand must be in spatial proximity to the NC surface, which is only possible if the native ligand (oleic acid/oleylamine) is replaced.…”
Section: Resultssupporting
confidence: 86%
“…Together with the changes in the PLQY of LiTFSI-treated CsPbBr 3 NC films, we also observed a slight red shift of their PL emission spectra (Figure S1), which is indicative of ligand exchange by the addition of LiTFSI to the NC solutions prior to spin-coating. Similar observations were recently reported on red-emitting LHP NC and were assigned to the highly dynamic/labile binding situation of oleic acid and oleylamine on the perovskite NC surface. , Therefore, both the enhanced PLQY and the spectral PL red shift indicate that the new ligand must be in spatial proximity to the NC surface, which is only possible if the native ligand (oleic acid/oleylamine) is replaced.…”
Section: Resultssupporting
confidence: 86%
“…31 During XPS, the NCs are subject to substantial charging and, while not all considerations for the reduction of Cd in CdSe may be transferable to Pb in CsPbBrI 2 , we argue that the general rational outlined by du Fossé et al is of central importance also in the present case: mZnTPP invokes a 0.5 eV increase in work function (Fig. 5(a)) and provides better dielectric screening (a higher permittivity) 26 compared to the native ligand. As du Fossé et al have shown, a reduced work function affects primarily the overall crystal and only to a lesser extent a localized state, such as Pb 0 .…”
mentioning
confidence: 47%
“…31 During XPS, the NCs are subject to substantial charging and, while not all considerations for the reduction of Cd in CdSe may be transferable to Pb in CsPbBrI 2 , we argue that the general rational outlined by du Fosse ´et al is of central importance also in the present case: mZnTPP invokes a 0.5 eV increase in work function (Fig. 5(a)) and provides better dielectric screening (a higher permittivity) 26 Thus, a promising strategy to further enhance the stability of perovskite NCs is the search for ligands that induce even larger work functions. We note that both degradation pathways -with and without mZnTPP -are preceded by the same core level energy shifts of Pb and Cs (Fig.…”
mentioning
confidence: 54%
See 2 more Smart Citations